2010
DOI: 10.1093/brain/awp343
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral white matter recovery in abstinent alcoholics—a multimodality magnetic resonance study

Abstract: Most previous neuroimaging studies of alcohol-induced brain injury and recovery thereof during abstinence from alcohol used a single imaging modality. They have demonstrated widespread microstructural, macrostructural or metabolite abnormalities that were partially reversible with abstinence, with the cigarette smoking potentially modulating these processes. The goals of this study were to evaluate white matter injury and recovery thereof, simultaneously with diffusion tensor imaging, magnetic resonance imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 50 publications
4
78
2
1
Order By: Relevance
“…25 By use of a variety of contemporary imaging methods, it has also been demonstrated that there are marked brain microstructural and macrostructural improvements even after relatively short periods of abstinence. 26 In summary, alcohol produces both structural and physiological changes in the brain. As with the effects of HIV infection on the CNS, alcohol produces the most striking changes in white matter structures.…”
Section: Effects Of Alcohol On the Brainmentioning
confidence: 99%
“…25 By use of a variety of contemporary imaging methods, it has also been demonstrated that there are marked brain microstructural and macrostructural improvements even after relatively short periods of abstinence. 26 In summary, alcohol produces both structural and physiological changes in the brain. As with the effects of HIV infection on the CNS, alcohol produces the most striking changes in white matter structures.…”
Section: Effects Of Alcohol On the Brainmentioning
confidence: 99%
“…Different analyses of white matter (FA vs. volume) provide different information about its structure (highly directional diffusion vs. higher density of connectivity fibers, respectively). Thus, both white matter volume results (Hupé et al 2011) andFA data (Jancke et al 2009;Rouw and Scholte 2007) are informative in synesthesia research, and the combination of both (Hanggi et al 2008) increases the detection power of anatomical studies (Gazdzinski et al 2010). Moreover, another type of data analysis, based on connectivity matrices derived from region-wise cortical thickness correlations, has demonstrated widespread connectivity alterations in graphemecolor synesthetes (Hanggi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[29,30]. The fastest brain tissue recovery was observed in sober individuals with the highest drinking intensity and basal brain reduction.…”
Section: Discussionmentioning
confidence: 95%